FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Faranty, - (2019)
This study aims to determine the factors that influence the quality of financial local government reports and the problems / constraints faced by OPD in the preparation of financial statements. financial statements have an important role in the formulation of development policies. The low quality of financial statements can provide accurate information for policy makers, information that is inaccurate can lead to inaccuracies in policy formulation that make a negative impact on institutional development. Based on the quality that is lower than the financial statements of local governments, this needs special attention. The factors studied were the influence of HR competencies, information technology, internal control systems, and regional financial accounting systems.The data collection of this study uses a questionnaire survey. The questionnaire was submitted to 145 South Tangerang City Regional Organization (OPD) employees who worked in the accounting / finance department, 141 questionnaires (97%) were returned to complete and can be processed. The collected data is processed using the SPSS version 25.0 program. The statistical method used to test the hypothesis is multiple linear regression analysis.The results of hypothesis testing are HR competencies, information technology, and regional financial accounting systems that have significant and significant influence on the quality of local government financial reports. Meanwhile, the internal control system does not have an influence on the quality of local government financial reports.